Electrode kinetics of porous Ni-3YSZ cermet operated in fuel cell and electrolysis modes for solid oxide cell application. (1st September 2021) - Monaco, Federico; Effori, Elisa; Hubert, Maxime; Siebert, Elisabeth; Geneste, Gregory; Morel, Bertrand; Djurado, Elisabeth; Montinaro, Dario; Laurencin, Jérôme
Highlights: Electrochemical characterizations of Ni-3YSZ electrode in SOFC and SOEC conditions. Electrochemical impedance spectra measured up to high steam partial pressure. Electrode microstructure reconstructed by synchrotron X-ray holotomography. Dynamic model with a micro kinetic elementary description for porous Ni-3YSZ cermet. Reaction pathways and rate-limiting steps in SOFC and SOEC modes. Abstract: The electrochemical reactions of hydrogen oxidation and steam reduction have been investigated for a porous cermet electrode made of Ni and 3YSZ. The electrochemical characterizations have been performed over a large range of gas compositions at 700°C. It has been shown that the fuel electrode response is activated by the potential under anodic current while a limiting current density appears under cathodic polarization. Moreover, the impedance diagrams exhibit a shape representative of a kind of finite-length Gerischer element with a low-frequency contribution sensitive to the steam content. To interpret these experimental results, a continuous dynamic model has been developed by describing the mass and charge transfers within the electrode. The reaction has been divided into a sequence of elementary steps considering two scenarios of charge transfer based on the oxygen and hydrogen spillover mechanisms. Three-dimensional reconstructions obtained by synchrotron X-ray nano-holotomography have been used to provide the cermet structural properties for the simulations. The numerical computations have shown that the hydrogen spillover scenario is the most appropriate mechanism to reproduce correctly the experiments. Besides, the electrode response is controlled by the charge transfer at triple phase boundary lengths, the oxygen vacancies migration in the 3YSZ network and a pure chemical surface process depending on the polarization. In fuel cell mode, desorption of water molecules from 3YSZ would co-limit the electrode response, while in electrolysis mode, the steam adsorption on Ni would become one of the rate determining steps. Finally, a sensitivity analysis has shown that surface diffusion would also play a key role in the electrode response.